2020
DOI: 10.3390/s20247035
|View full text |Cite
|
Sign up to set email alerts
|

Setup, Test and Validation of a UHF RFID System for Monitoring Feeding Behaviour of Dairy Cows

Abstract: Feeding behaviour can be used as an important indicator to support animal management. However, using feeding behaviour as a tool for dairy cow management an automatic sensor system is needed. Hence, the objective of this study was to setup, test and validate a ultra-high frequency (UHF) radio-frequency identification (RFID) system for measuring time dairy cows spent at the feed fence using two types of passive UHF ear tags. In a first experiment, the reading area of the system was evaluated in two antenna posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…RFID systems have been used to detect feeding behaviour [118][119][120], drinking behaviour [121,122] and supplement intake [123] based on proximity to the feed bunk, water point and mineral lick block, respectively. Toaf et al [124] found that an RFID-based ear tag recording of brush proximity was not yet a reliable representation of grooming behaviour as some animals spent a relatively large portion of time standing idle close to the brush, resulting in false positives.…”
Section: Radio Frequency Identification (Rfid)mentioning
confidence: 99%
“…RFID systems have been used to detect feeding behaviour [118][119][120], drinking behaviour [121,122] and supplement intake [123] based on proximity to the feed bunk, water point and mineral lick block, respectively. Toaf et al [124] found that an RFID-based ear tag recording of brush proximity was not yet a reliable representation of grooming behaviour as some animals spent a relatively large portion of time standing idle close to the brush, resulting in false positives.…”
Section: Radio Frequency Identification (Rfid)mentioning
confidence: 99%
“…In addition, the RFID system inevitably has to consider the signal collision problem of multiple tags entering the reading area at the same time, and the nRF24LE1 integrates the carrier monitoring function, which can accurately monitor whether the current working channel has interference. erefore, the system chooses nRF24LE1 as the core chip, which can not only meet the requirements of low cost, low power consumption, high integration, and high performance, but also enhance the system's ability to prevent collisions and identify moving targets [13,14].…”
Section: Hardware Module Designmentioning
confidence: 99%
“…There were two main reasons: (1) the total number of samples in these two intervals was small, so even a small amount of false detection had a relatively large impact on the results; (2) the deformation of the tag led to an increase in false detection boxes that overlapped with the target but did not fully contain the numbers on the tag. There were only three ID tags in interval (7), which had fewer samples. When drawing its P-R curve, the accuracy and recall rate were both 100% with the confidence threshold set to 0.7, so its AP50 was 100%.…”
Section: Deformation and Brightness Robustnessmentioning
confidence: 99%
“…Radio frequency identification (RFID) is an individual identification method commonly used on large commercial dairy farms. RFID enables the recording of individual information, feeding information [7,8], and milk production [9,10] of dairy cows by reading tags attached to their bodies (usually ear tags) with wireless transmission technology. Compared with traditional methods, the reliability of information and the real-time information acquisition performance of RFID are improved.…”
Section: Introductionmentioning
confidence: 99%